Banks are different: why bank-based versus market-based lending is a false dichotomy - Carolyn Sissoko (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
This paper introduces modern readers to 'banking theory', that is, to the understanding of the banking system that was held by academics and practitioners in the early years of the twentieth century. This theory contrasts with the theoretic framework that views banks as intermediaries that receive deposits and invest deposits in assets. The basic elements of banking theory are related to the modern network effects literature, and a bank-centered view of the financial system is derived: all demand and short-term bank liabilities, including contingent liabilities, are potential money and near-money assets; and any non-bank liabilities that have monetary properties derive them from the banking system. This framework is then used to evaluate modern money markets, and the paper proposes that bank-liability-based measures of the money supply be developed, and that regulators recognize that contingent bank liabilities often function as a substitute for deposits and should be regulated similarly.
Keywords: B10; B50; E5; 330; banking theory; circuit theory; contingent liabilities; money market; network effects